2021
DOI: 10.48550/arxiv.2104.13032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High contrast imaging at 10 microns, a search for exoplanets around: Eps Indi A, Eps Eri, Tau Ceti, Sirius A and Sirius B

P. Pathak,
D. J. M. Petit dit de la Roche,
M. Kasper
et al.

Abstract: Context. The direct imaging of rocky exoplanets is one of the major science goals for upcoming large telescopes. The contrast requirement for imaging such planets is challenging. However, the mid-IR (InfraRed) regime provides the optimum contrast to directly detect the thermal signatures of exoplanets in our solar neighbourhood. Aims. We aim to exploit novel fast chopping techniques newly developed for astronomy with the aid of adaptive optics to look for thermal signatures of exoplanets around bright stars in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…A planet with a period P = 7.37 ± 0.07 yr of similar mass but a nearly circular orbit was confirmed by Mawet et al (2019). The prominent dusty debris disk of ǫ Eri has an inner radius of ∼ 30 au (Greaves et al 1998) possibly caused by another giant planet at this distance (Hatzes et al 2000)-however, no such object has been found by direct imaging (Pathak et al 2021).…”
Section: The Planet Of ǫ Erimentioning
confidence: 92%
“…A planet with a period P = 7.37 ± 0.07 yr of similar mass but a nearly circular orbit was confirmed by Mawet et al (2019). The prominent dusty debris disk of ǫ Eri has an inner radius of ∼ 30 au (Greaves et al 1998) possibly caused by another giant planet at this distance (Hatzes et al 2000)-however, no such object has been found by direct imaging (Pathak et al 2021).…”
Section: The Planet Of ǫ Erimentioning
confidence: 92%
“…Two of the stars are known to host Jupiter-like planets, namely Eri b (1.56MJ orbiting at 3.39 au, Hatzes et al 2000;Benedict et al 2006;Mawet et al 2019) andInd b (3.25MJ orbiting at 11.55 au, Feng et al 2019), detected via radial velocity observations. Recent high-contrast imaging at 10µm by Pathak et al (2021) with VISIR were not able to directly detect these planets. Eri is still surrounded by a debris disk with an estimated age of 0.4 Gyr.…”
Section: Description Of Samplementioning
confidence: 98%
“…While reflected light imaging [e.g., 46] will also enable the study of many of these same planets, its combination with mid-IR imaging is needed to break the degeneracy between radius and albedo. Indeed, such observations have already started to place limits on the properties of planets within a handful of systems [e.g., 16,[47][48][49].…”
Section: Exoplanet Science With High-contrast Mid-ir Imagingmentioning
confidence: 99%